The adaptability of rural healthcare workers' knowledge, skills, and attitudes during public health emergencies: insights from the COVID-19 response in Itilima district, Simiyu, Tanzania - Msegu, Elia; Konje, Eveline; Tupa, Teckla; Basinda, Namanya; Gwimile, Mlemile S.; Ngallaba, Teddy; Marwa, Fredy (Frontiers in Disaster and Emergency Medicine, 2024)
Community Health Workers (CHWs) are the first contact between the community and health services in multiple rural areas in Tanzania. Therefore, Community Health Workers are set to play a crucial role in emergencies and disasters. This cross-sectional study assessed the readiness of CHWs in Itilima concerning preventing the spread of COVID-19. A total of 190 CHWs and 30 stakeholders were interviewed using quantitative and qualitative methods respectively.Multivariate linear regression model was used for quantitative data while thematic analysis was used for qualitative data. The study revealed that 140/190 (73%) CHWs had adequate knowledge of COVID-19, with 126/190 (66.32%) after receiving on-job training on COVID-19. There was no association between demographic characteristics and CHWs' knowledge of COVID-19. Indepth interviews (IDIs) highlighted that the majority of the CHWs were equipped with PPEs and other working tools to aid their role in response to COVID-19. Challenges such as incentive inadequacy and insufficient working tools were among the major setbacks highlighted by the CHWs during the IDIs. CHWs appear to be adaptable and provide relevant feedback thus can take part in emergencies and disasters when capacity building is done.